Implementation of Problem Based Learning Model to Improving Students' Critical Thinking Skills in Morals Learning At MTs Mu'allimin Katekan - Dhea Hanifa Azzahra; Husna Nashihin; Ana Sofiyatul Azizah (PT Mutiara Bustan Ilmu, 2025)
The moral degradation among students—such as bullying, inappropriate social interactions, and low empathy—emphasizes the urgency of Akhlak (Islamic moral education) that fosters noble character and higher-order thinking skills. Critical thinking enables students to analyze information, assess moral values, and make logical, responsible decisions amid the rapid digital information flow. This study explores the preparation, implementation, and evaluation of the problem-based learning (PBL) model to enhance students’ critical thinking in Akhlak subjects at MTs Mu’allimin Katekan. Using a qualitative descriptive design, data were collected from teachers, students, and classroom observations through interviews, documentation, and observation. Data were analyzed through reduction, presentation, and conclusion drawing, with validity ensured by source and technique triangulation. Results show that PBL, applied through preparation, implementation, and evaluation stages, effectively fostered students’ confidence, argumentation, collaboration, responsibility, and empathy. Although some students were still passive and time was limited, PBL significantly improved critical thinking, communication, collaboration, and moral character.